Climate Smart Agriculture: Ghana - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
As part of ongoing research in East and West Africa, CCAFS spent time in the field in Ghana to determine the challenges that could prevent farmers from adopting climate smart agricultural techniques. Lucy, a farmer in Lawra, Ghana, has enthusiastically adopted composting to increase soil fertility on her farm. April-May 2013. Photo: C Peterson (CIAT/CCAFS)